Wireless sensor networks in the internet of things: review, techniques, challenges, and future directions - Fu Zijie; Mahmood A. Al-Shareeda; Murtaja Ali Saare; Selvakumar Manickam; Shankar Karuppayah (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Wireless sensor networks (WSN) are an emerging multidisciplinary intersection of cutting-edge research fields, and their advantages in terms of freedom of formation, high signal-to-noise ratio, high strength, and unattended, which makes WSN have good prospects for application in the field of internet of things (IoT). Considering all the benefits that WSN offer, this paper reviews the development history of wireless sensor networks internet of things (WSN-IoT), analyses the technologies used by sensors in the IoT, and illustrates the future developing patterns and remaining challenges, in conjunction with the main technologies in the perception layer of the current network of things industry.